2021
DOI: 10.1063/5.0064342
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of nitroxide structure upon 1H Overhauser dynamic nuclear polarization efficacy at ultralow-field

Abstract: The efficacy in 1H Overhauser dynamic nuclear polarization in liquids at ultralow magnetic field (ULF, B0 = 92 ± 0.8 µT) and polarization field ( B p = 1–10 mT) was studied for a broad variety of 26 different spin probes. Among others, piperidine, pyrrolidine, and pyrroline radicals specifically synthesized for this study, along with some well-established commercially available nitroxides, were investigated. Isotope-substituted variants, some sterically shielded reduction-resistant nitroxides, and some biradic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…The Overhauser effect relies on incoherent electron-nuclear cross-relaxation mediated by dipole, scalar, or isotropic hyperfine interactions [14]. Unlike thermal mixing or the solid or cross effect, the Overhauser effect allows the hyperpolarization of liquids at room temperature [46]. This unique advantage allows for continuous in situ, ex vivo, or even in vivo hyperpolarization of the sample itself, eliminating the need for a hyperpolarized bolus.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Overhauser effect relies on incoherent electron-nuclear cross-relaxation mediated by dipole, scalar, or isotropic hyperfine interactions [14]. Unlike thermal mixing or the solid or cross effect, the Overhauser effect allows the hyperpolarization of liquids at room temperature [46]. This unique advantage allows for continuous in situ, ex vivo, or even in vivo hyperpolarization of the sample itself, eliminating the need for a hyperpolarized bolus.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, in vivo OMRI is generally performed in the low field range, with the optimal field strength depending on the sample geometry and the specific absorption rate (SAR), which must be considered to prevent sample heating [44,52,53]. Nev-ertheless, in vivo experiments on small animals have been performed using OMRI [46,48]. The success of OMRI depends on the presence of special hyperpolarizing contrast agents (HCAs) that facilitate the transfer of polarization from free electrons, such as free radicals, to nuclear spins, such as water protons, thereby enhancing the MRI signal [14,46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, these mechanisms work best at a sample temperature of ≤100 K and can give large signal enhancements of ≥100 in the presence of carefully selected polarizing agents. , In liquids, only the OE mechanism is active, which requires the time-dependent interaction between electrons and nuclei on a time scale comparable with the reciprocal of the electron Larmor frequency (1/ω e ). For this reason, the liquid-state OE is most effective at low magnetic field strength. Nonetheless, it has been recently shown that the OE can yield significant 13 C (ε ≥ 600) and 31 P (ε ≥ 160) signal enhancements at magnetic fields of 9.4 and 14 T, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Complicated hyperfine structure and line broadening in the EPR spectra of sterically shielded nitroxides makes them inefficient in EPRI and OMRI applications, where radicals with a minimal number of narrow lines are required for better resolution and enhancement. Broadened spectral lines can also hamper analysis of molecular dynamics using spin labeling and EPR . A better understanding of the factors affecting the hyperfine structure in the EPR spectra of sterically shielded nitroxides could help in the molecular design of better structures.…”
Section: Introductionmentioning
confidence: 99%